Psychometric properties of a Portuguese version of the Subjective Happiness Scale - Spagnoli, P. (2014)
The Subjective Happiness Scale (SHS) constitutes an instrument for assessing subjective happiness. This study aims to present the validation of the SHS in a Portuguese adult population. A large representative sample (1,017 participants), from five different age groups was considered. Configurational invariance of the unidimensional structure of the scale was tested through multi-group confirmatory factorial analysis, and reliability and criterion-validity were investigated. The results support the single factorial structure and reliability of the SHS. Furthermore, the SHS correlated positively with the Satisfaction with Life Scale, thus supporting its criterion validity. Therefore, the Portuguese version of the SHS is a valid instrument to use with an adult Portuguese Sample.